Between past and future: memory and mourning in the stories of Okwiri Oduor and Ndinda Kioko - Awuor, Nicholas Amol (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2020)
This study investigates the literary activities of two emerging female Kenyan writers, Claudette Okwiri Oduor and Jacqueline Ndinda Kioko, both of whom are award-winning authors. Oduor won the 2014 Caine Prize for African Writing while Kioko bagged the Wasafiri New Writing Fiction Award 2017. It examines specifically how the writers deal with memory and mourning in negotiating between the past and future. I explore how their fictional and non-fictional narratives assist individuals and groups to confront loss, reconstruct new identities, and renegotiate belonging amidst personal and social upheaval. The fictional narratives at the centre of this research are Oduor's "The Plea Bargain" (2011), "My Father's Head" (2013) and "Rag Doll" (2014), and Kioko's "Sometime Before Maulidi" (2014) and "Some Freedom Dreams" (2017). The study explores the themes of mental illness, existential crisis, and fragmentation, and considers bereavement, queer relationships, cultural freedom, and social recognition. The research further considers the active participation of these two writers in Kenya's contemporary literary-cultural conversations, which span different genres and various media platforms, including blogs, YouTube clips, online magazines, and social media networks in dialogue with other writers. . I trace the significance of the literary-cultural link these authors have with their local, continental, and global counterparts in countries like Uganda, Nigeria, and South Africa. The link finds expression through their (in)direct association with some of the new online publishing outlets in Kenya like Jalada Africa, Enkare Review, and Kikwetu. More importantly, their shared participation in and association with such international awards and scholarships as the Commonwealth Short Story Prize, Kwani Trust Manuscript Project, and Miles Morland Foundation is integral in apprehending contemporary literary exchanges and multidirectional flows of publishing in Africa and beyond. I equally illustrate how mentorship of younger writers through local writers' organisations and collectives like AMKA and Writivism help in the formation of an alternative canon other than the mainstream. The study affirms that the authors seem to transcend the boundaries of production and circulation by fluidly moving between electronic and non-electronic platforms, thus mimicking the memory production of remembering, repeating, and working through.
Keywords: Women authors, Kenyan; Oduor, Okwiri -- The plea bargain; Oduor, Okwiri -- My father's head; Oduor, Okwiri -- Rag doll; Kioko, Ndinda -- Sometime before Maulidi; Kioko, Ndinda -- Some freedom dreams; Women and literature -- Africa; Bereavement -- Fiction; Culture in literature; Liberty in literature